Women's Collections: Libraries, Archives, and Consciousness, 1st edition - Hildenbrand, Suzanne (Routledge, 2020)
This book, first published in 1986, analyses women's collections in institutional and private establishments in the United States. It focuses on the development of the collections as a result of feminist advances in activism and scholarship, and the need for collections to reflect the shift to a necessary woman-centredness in their holdings.